2008
DOI: 10.1007/s11999-008-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Recovery of Balance Control after Total Hip Arthroplasty

Abstract: Hip osteoarthritis leads to chronic pain and deteriorated joint function, which affect weightbearing and balance during gait. THA effectively restores hip function but it is not known whether THA restores balance during gait. We hypothesized patients would have greater frontal plane and smaller sagittal plane center of mass-center of pressure inclination angles preoperatively compared with control subjects, and THA would improve these inclination angles by 16 weeks postsurgery. Compared with control subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 41 publications
0
14
0
4
Order By: Relevance
“…However, relatively little direct objective comparison data have been published comparing minimally invasive THA techniques with one another or with an established THA technique [11,18,29]. Using comprehensive gait analysis and strength testing, we previously investigated the early (2-month) functional outcome after THA, with a randomized clinical trial of the two-incision and mini-posterior surgical approaches and found an advantage for the miniposterior approach [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively little direct objective comparison data have been published comparing minimally invasive THA techniques with one another or with an established THA technique [11,18,29]. Using comprehensive gait analysis and strength testing, we previously investigated the early (2-month) functional outcome after THA, with a randomized clinical trial of the two-incision and mini-posterior surgical approaches and found an advantage for the miniposterior approach [16].…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, relatively little direct comparison data have been published comparing minimally invasive THA techniques with one another or with an established THA technique [9,13,22]. We were particularly interested to see if one widely touted technique, the two-incision approach, provided substantial early functional benefits over another form of THA.…”
Section: Discussionmentioning
confidence: 99%
“…In hip arthroplasty patients, decrease in joint function and muscle strength increases risk for falling, and patients might experience fear of falling during activities of daily living (ADL) resulting from permanent impacts on joint function (Lugade, Klausmeier, Jewett, Collis, & Chou, 2008;Nagai et al, 2014). Investigation of the relationship of these parameters with HRQoL may be important in terms of improving quality of life.…”
Section: Introductionmentioning
confidence: 99%